Funding a Peoples' Food Justice Geography? Community–Academic Collaborations as Geographic Praxis. Issue 6 (19th September 2021) - Block, Daniel R.; Reynolds, Kristin
Abstract : Community–academic collaborations that value experience-based knowledge alongside institutional ways of knowing have long been of interest in geography. In 1984, Harvey proposed a "peoples' geography" that would integrate nonacademic knowledge into the field, increasing geography's potential to help create a just world. Recent community–academic food justice collaborations have taken up this proposition through initiatives addressing issues from food access to dismantling racism, suggesting possibilities for a "peoples' food justice geography." Grant funding is often necessary for such work and might allow for more equitable participation or increase project reach but can necessitate redistribution of time spent on project activities, reinforce hierarchies, or be counterproductive to systemic change. If funding for community–academic food justice collaborations is to help create an inclusive and nonelitist geographic praxis, deeper understanding of its effects is essential. This article explores these possibilities. Drawing from an examination of the U.S. food funding landscape and field experiences in Chicago and New York, we show how funding, or lack thereof, can affect such collaborations. We argue that despite sustained debate about philanthropy and social change, with long-term vision, funding can advance food justice goals. We conclude with reflections on the relevance for a peoples' food justice geography.